2007
DOI: 10.1007/s10661-006-9519-8
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Biofilm-associated Legionella pneumophila on Different Substrata in Model Cooling Tower System

Abstract: Cooling towers have the potential to develop infectious concentrations of Legionella pneumophila. Legionella counts increases where biofilm and warm water temperatures are present. In this study, biofilm associated L. pneumophila and heterotrophic bacteria were compared in terms of material dependence. Model cooling tower system was experimentally infected by L. pneumophila standard strain and monthly monitored. Different materials were tested for a period of 180 days. The lowest L. pneumophila and heterotroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 31 publications
1
14
0
1
Order By: Relevance
“…It can be because of ubiquity of this micro-organism, particularly in humid climate such as BA [17,18]. The result of this study is near to those of the last studies on this topic [19,20].…”
Section: Resultssupporting
confidence: 73%
“…It can be because of ubiquity of this micro-organism, particularly in humid climate such as BA [17,18]. The result of this study is near to those of the last studies on this topic [19,20].…”
Section: Resultssupporting
confidence: 73%
“…Erdem et al (2008) found that the HPC population associated with stainless steel coupons was higher than that associated with glass slides, but a higher density was associated with galvanised stainless steel and smaller plastic polymers to polyvinyl chloride, polyethylene and polypropylene. Turetgen and Cotuk (2007) investigated biofilm-associated Legionella pneumophila and heterotrophic bacteria in terms of material dependence and found that HPC values were in the following order: stainless steel>glass> polyvinyl chloride. A higher density of HPC associated with galvanised steel coupons when compared to copper coupons was described by Doğruöz et al (2009a).…”
Section: Discussionmentioning
confidence: 99%
“…types of surface materials, water temperature, pH, microbial quality of intake water, concentration and quality of nutrients, as well as the presence of residual biocide (Zacheus et al 2000;Markku et al 2006;Turetgen and Cotuk 2007;Doğruöz et al 2009b). Due to economical, operational and public health reasons, both bulk water and the biofilm layer of cooling towers should be monitored and controlled in view of microbial burden.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Występowaniu zanieczyszczenia mikrobiologicznego wody, w tym pałeczkami Legionella, sprzyja m.in. obecność biofilmu, osadów, korozja, niskie stężenia środków dezynfekcyjnych, zastój oraz temperatura wody w zakresie 25,4-42,5°C (3)(4)(5).…”
Section: Badania Poziomu Zanieczyszczeń Mikrobiologicznych Powietrzaunclassified